2016
DOI: 10.1186/s12929-016-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3/VDR resists diet-induced obesity by modulating UCP3 expression in muscles

Abstract: BackgroundThe impact of vitamin D3 (VD3) on obesity has been reported in the past. Our study was aimed at investigating the possible mechanisms by which VD3 affects obesity induced by a high fat diet.MethodsEight-week-old C57BL/6 J male mice were fed a normal- or high-fat diet for 9 weeks and were treated with a gavage of vehicle (corn oil) or cholecalciferol (50 μg/kg, daily). Body weight, white adipose tissue weight, blood lipid and glucose levels were measured. In addition, we investigated the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…25(OH)D 3 and 1,25(OH) 2 D 3 repletion attenuated perturbations of UCPs and ATP contents in adipose tissues and muscle in Ctns −/− mice. 1,25(OH) 2 D 3 suppresses UCPs expression in primary brown adipocyte and suppresses differentiation and mitochondrial respiration of brown adipocyte 1,25(OH) 2 D 3 /VDR by binding to the promoter region of the UCP3 gene and modulating UCP3 gene transcription and subsequent energy metabolism in muscle …”
Section: Discussionmentioning
confidence: 99%
“…25(OH)D 3 and 1,25(OH) 2 D 3 repletion attenuated perturbations of UCPs and ATP contents in adipose tissues and muscle in Ctns −/− mice. 1,25(OH) 2 D 3 suppresses UCPs expression in primary brown adipocyte and suppresses differentiation and mitochondrial respiration of brown adipocyte 1,25(OH) 2 D 3 /VDR by binding to the promoter region of the UCP3 gene and modulating UCP3 gene transcription and subsequent energy metabolism in muscle …”
Section: Discussionmentioning
confidence: 99%
“…It is a key hormone involved in calcium and phosphorous balance with several derivatives (Muscogiuri et al, 2017). Vitamin D receptor (VDR) is found in the pancreatic β cells and insulin response tissues such as skeletal muscle and adipose tissue (Fan et al, 2016). Studies showed that vitamin D affected glucose utilization in VDR-dependent manner in muscle and adipose tissue and activated PPARδ, which is a transcription factor involved in fatty acid metabolism (Grammatiki et al, 2017).…”
Section: Vitaminmentioning
confidence: 99%
“…1,25-dihydroxyvitamin D3 suppresses expression of UCPs, cell differentiation as well as mitochondrial respiration in brown adipocytes 33,34 . Recent data also confirmed that vitamin D3 modulates UCP3 expression in muscle via the binding site consensus sequences of VDR on the UCP-3 promoter region 35 . Muscle pro-fibrotic factor Transforming growth factor-β1 (TGF-β1) 1.1 ± 1.0 1.1 ± 0.6 3.4 ± 0.4 A,C 1.5 ± 0.4…”
Section: Discussionmentioning
confidence: 64%